2020
DOI: 10.1089/ast.2019.2087
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Elemental Signatures of Microbes in Martian Mudstone Analogs Using High Spatial Resolution Laser Ablation Ionization Mass Spectrometry

Abstract: The detection and identification of biosignatures on planetary bodies such as Mars in situ is extremely challenging. Current knowledge from space exploration missions suggests that a suite of complementary instruments is required in situ for a successful identification of past or present life. For future exploration missions, new and innovative instrumentation capable of high spatial resolution chemical (elemental and isotope) analysis of solids with improved measurement capabilities is of considerable interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
(60 reference statements)
0
17
0
Order By: Relevance
“…In recent studies, the capabilities of fs-LMS to identify bio-organic material within geological samples were investigated in the context of instrument selection for the next planetary missions [33]. In total, 14 Martian mudstone analogue samples were investigated regarding their elemental composition.…”
Section: Geological and Geochemical Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, the capabilities of fs-LMS to identify bio-organic material within geological samples were investigated in the context of instrument selection for the next planetary missions [33]. In total, 14 Martian mudstone analogue samples were investigated regarding their elemental composition.…”
Section: Geological and Geochemical Samplesmentioning
confidence: 99%
“…The mass spectrometric analysis of these data allows for complex correlation analyses between isotopes and elements leading to improved quantification and identification of molecular parent compounds, and their location within the sample volume. These interesting new features can be of importance in analysing highly heterogeneous materials, including micrometre-sized mineralogical grains or identifying extant or fossilised microorganisms within rocks and soils [28,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Elemental distribution of biogenic elements or molecules at micron scales can be detected using techniques such as LDI-MS or SIMS. For example, Riedo et al (2020) was able to distinguish biologically relevant elements, such as H, C, S, N, P, and Fe, between microbial life and its mineral matrix in a biologically-spiked Mars analog sample via a high spatial resolution LDI-MS. Similarly, Tulej et al (2015) was able to study the elemental composition of Terran-based natural samples using LDI-MS, and used the information to distinguish the differences between microfossils and mineral matrix background.…”
Section: Terran-based Chemical Biosignatures Revealed By Mass Spectrometrymentioning
confidence: 99%
“…Larger molecules have also been investigated using MS imaging, such as the characterization of lipid biomarkers in modern microbial mats and fluid inclusions using a TOF-SIMS (Siljeström et al, 2010;Leefmann et al, 2013). The spatial resolution of MS imaging approaches such as MALDI have typically been on the order of 10 s of microns (Cornett et al, 2007;Riedo et al, 2020), implying the requirement of multicellular structures to ensure biological detection, but advances in matrix application has allowed for 1.4 µm resolution in a study of metabolite, lipid, and peptide arrangements (Kompauer et al, 2017). As MS imaging resolution continues to improve toward that of a single microbial cell, the approach will gain relevance in an astrobiological context, where single-cell detection is a priority.…”
Section: Terran-based Chemical Biosignatures Revealed By Mass Spectrometrymentioning
confidence: 99%
“…LIMS modification of this instrument has been reported to measure ppbw level trace elements and routinely measure fine chemistry from a variety of samples ( Riedo et al, 2013a ; Neuland et al, 2016 ; Wiesendanger et al, 2017 ). Moreover, a number of reports have indicated that LIMS, particularly fs-LIMS, might be applicable to the detection of faint signatures of life from microscopic inclusions ( Tulej et al, 2015 ; Wiesendanger et al, 2018 ) and low-biomass Martian analogs ( Stevens et al, 2019 ; Riedo et al, 2020 ). However, the field of study of early and primitive life remains profoundly complex ( Brasier and Wacey 2012 ; Westall et al, 2015 ; Wacey et al, 2016 ) with no single chemical criterion that can be assigned as definitive proof of biogenicity.…”
Section: Introductionmentioning
confidence: 99%